The difficult relationship between historical ordoliberalism and Adam Smith - Karen Horn (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2019)
Ever since the global financial crisis of 2008, interpreted by some observers as a foreseeable failure of "unfettered" capitalism, the German intellectual tradition of ordoliberalism has been meeting with increased interest. Its emphasis on good government, appropriate rules and institutions makes it attractive. Welcome as this may be, however, that trend may impact the reception of the works of Adam Smith in a problematic way, since the key historical figures of ordoliberalism reject his theory vigorously, even though, from today's perspective, their concerns and policy recommendations look very parallel to his. Their common hope is human flourishing. Just like the Scot, the broad scope of their vision encompasses society as a whole, not just the market; they are concerned with ethics, not just economics. But what, then, can solve the puzzle of this implausible rejection, by which the ordoliberals contribute to a deep-rooted prejudice against Smith? In this paper, Karen Horn takes stock of their concrete criticisms, which turn out to be based on a narrow understanding of Smith's work. She suggests that it is religion that stands at the root of the explanation, though situational elements may also play a role. The essential contentious point seems to be what the ordoliberals take for the Scot's naïve belief in natural harmony, the sources of which they see in his stoicism and possible deism. The deeper problem for them with Smith is the pagan flavour and the systematic normative relativism of an essentially evolutionary approach to human values.
Keywords: B12; B3; 330; Ordoliberalism; Adam Smith; History of economic thought; Natural harmony